The Metaverse as Lab to Experiment with Problems of Organized Complexity - Devisch, Oswald (Complexity and Planning, 2012)
In 1948 Warren Weaver, later accredited with being one of the founding fathers of complexity theory, introduced the notion 'Problems of Organized Complexity', referring to complex problems displaying essential features of organization, and proclaimed simulations as the tool to tackle these problems. Since Weaver's proclamation, (computer) simulations have indeed been explored, also within the field of planning, to operate in - in the case of planning - complex physical settings. Such explorations typically start off as theoretical experiments, but seldom make it to the planning practice.